Evaluation of the Effects of Different Surface Configurations on Stability of Miniscrews. (1st July 2013) - Topcuoglu, Tolga; Bicakci, A. Altuğ; Avunduk, M. Cihat; Sahin Inan, Z. Deniz
Abstract : Introduction . The aim of this study was to analyze the effects of screw design and force application on the stability of miniscrews, using RTT, SEM, and histomorphometric analyses. Materials and Methods . Eighty cylindrical, self-drilling, and Ti6Al4V alloy miniscrews (1, 6 × 6 mm) were used. Four mini-screws were inserted in fibulas of each rabbit, and 115  G of force was immediately applied. Four miniscrews were inserted in the other fibula, on which no force was applied. Eight weeks after insertion, osseointegration between miniscrew and the surrounding bone was evaluated by the histomorphometric analyses, SEM, and RTT. Kruskal-Wallis and the paired t -tests were used for statistical analysis. Results . Values obtained from Group I were significantly higher than those of the other loaded groups (P   < . 05 ). There were no differences in RTT scores among Groups II, III, and IV. Similar findings were also observed for unloaded mini-screws. There was no significant difference between Groups I and I C, while the differences between loaded and unloaded controls for each miniscrew were statistically significant. Conclusions . Immediate loading of miniscrews does not impair screw stability. Also, the diameter of miniscrew and more frequent thread pitches have a positive effect on stability; however, length of miniscrews does not have a significant effect on the stability.